Agreeing/Disagreeing in a Dialogue: Multimodal Patterns of Its Expression - Hunyadi, Laszlo (Frontiers in Psychology, 2019)
Multimodality is a key property of communication. Even though the main channel of exchanging information is textual, the written text also relies on paralinguistic means to convey additional information using various kinds of punctuation. Speech, too, is always present in contributing to the understanding of the wider scope of the context, represented – in some restricted forms means, including typography, typesetting and style. Gestures are also part of the text in its broader sense: public stage performances necessarily accompany the text, too. The complex of text, speech and gestures can be understood as a set of unified multimodal patterns that progress in time. This paper offers a comprehensive insight in the temporal structure of dialogue interaction through the study of the multimodal expression of agreement/disagreement in the HuComTech Corpus, presenting patterns of behavior discovered using the research environment Theme.